Moros y cristianos, indios y españoles: Esquema de la conquista del otro - Gómez García, Pedro (1992)
A picturesque and folkloric vision of popular customs leads one to get lost in an evanescent aroma; the sensation can be intense, but a minimal understanding of what is repeated so religiously from time to time will be missing. When scholars of popular culture arrive, they begin to compile oral traditions, festivals, rites, music and dances, recipes and remedies, the life cycle, the agricultural cycle... Thus, for example, they come to catalog information on the festivals of many localities of a province or a region. They accumulate a large amount of data and observations, hardly exceeding a certain state of ethnographic fragmentation, dispersion and disconnection of knowledge.